Porous Ni-Cr-Mo-Cu alloys fabricated by elemental powder reactive synthesis. (22nd September 2021) - Yang, Junsheng; Li, Xide; Lv, Li; Liu, Xiaopeng; Zou, Haoran; Zhang, Chuo; Xiong, Lieqiang; Liu, Yuzuo
Abstract: Fabrication of porous Ni-Cr-Mo-Cu alloys is available through Ni, Cr, Mo and Cu elemental powder reactive synthesis at the sintering temperature of 1150 °C. The pore structures, including swelling behavior, open porosity, pore size and viscous permeability of the porous Ni-Cr-Mo-Cu alloys are systematically investigated. The results revealed that the parameters of pore structure firstly increased, and then decreased with the increase of the sintering temperature. When the sintering temperature rose to 1000 °C, the volume expansion, open porosity and viscous permeability of porous Ni-Cr-Mo-Cu alloys reached the peak value of 8.0%, 41.6% and 17.2 μ m 2, respectively. In addition, it was confirmed that the pore structure evolution was based on three stages, that is, in the low temperature section before stearic acid decomposition, the formation of pores was initiated by the volatilization of pore-forming agent and the interstitial pores of green compact; when the temperature was lower than 1083 °C, the increase of open porosity was mainly due to the Kirkendall effect caused by solid partial diffusion; while, when the temperature is within the range of 1083 ∼ 1150 °C, the shrinkage behavior at high temperature and a small amount of metal solution formed by the unreacted Cu led to decrease in pore structure parameters.